Mobilidade de íons em um cambissolo haplico alumínico submetido a aplicação de calcário e gesso agrícola - Silva, Elayne Cristina da (2010)
Many soils in the state of Parana are acidic in their natural state, with levels of aluminum in the shape and levels that are toxic to plants, this leads to the need for use of agricultural lime in the soil. Limestone is the most used corrective, but has slow mobility in the soil profile, but is slow its correctness beyond the layer of incorporation. In this sense, the use of gypsum now has in recent years, a special interest, because this has important chemical and physical characteristics necessary to be used as conditioner subsurface layers. This study was conducted to evaluate the vertical mobility of cations through soil columns after application of limestone, gypsum and a mixture of gypsum and limestone, submitted to percolation of water from a Cambissol Haplic Aluminic Irati municipality of in Parana State, this soil has a high amount of aluminum, and is widely used for growing crops, but little studied. The experiment was conducted in the in the laboratory, we used PVC columns with 8 cm diameter and 35 cm tall, sectioned and applied to water, simulating the average annual rainfall of 1245 mm in the region, split applications, three of percolations 450 mL, one every 15 days. After the soils were analyzed: pH, C, Ca, Mg, Al3+, concentration extractable P and K, H + Al (potential acidity), S (sum of bases) and CTC (capacity cation exchange) , base saturation (V), aluminum saturation (Al) and by atomic absorption was analyzed metals (Cu, Cr, Ni, Zn, Pb, Fe and Mn) easily exchangeable through leaching. Observe that, for the Cambisol study, the setting meets the needs of correction of pH, neutralization, Al3+, retention of bases and nutrients just for the treated layer, but with very slow process of leaching. The mixture with gypsum in lime facilitates this process by increasing the amount of copper, but increasing the mobility of metals.